2020
DOI: 10.1053/j.ajkd.2019.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Kidney Function Outcomes Following RAAS Inhibition in Patients With Heart Failure With Reduced Ejection Fraction

Abstract: Angiotensin-converting enzyme (ACE) inhibitors are beneficial in heart failure with reduced ejection fraction (HFrEF). We sought to describe longitudinal trends in estimated glomerular filtration rate (eGFR) in HFrEF and how ACE-inhibitor therapy influences these changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 32 publications
(34 reference statements)
0
22
0
Order By: Relevance
“…In addition, baseline CKD should not preclude the utilization of ACE‐I/ARBs as their treatment effects are maintained as demonstrated by several renal sub‐analysis of the landmark trials (CONSENSUS, SOLVD, SAVE, ATLAS, Val‐HeFT, CHARM‐Added, CHARM‐Alternative and HEAAL) 63 . However, post‐hoc analysis of the landmark ACE‐I trials in HF show that ACE‐I do not reduce the slope of GFR decline in comparison to patients assigned to placebo, but the short duration of follow‐up and early assessment of eGFR limit the interpretation of slope changes 64,65 . In contrast, in patients with diabetes (with or without HF), ACE‐I and ARBs do reduce the slope of GFR decline over time in trials of similar duration, which probably relates to the fact that diabetes is associated with more intraglomerular hypertension 68 .…”
Section: Renal Effects Of Established Guideline‐recommended Heart Fai...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, baseline CKD should not preclude the utilization of ACE‐I/ARBs as their treatment effects are maintained as demonstrated by several renal sub‐analysis of the landmark trials (CONSENSUS, SOLVD, SAVE, ATLAS, Val‐HeFT, CHARM‐Added, CHARM‐Alternative and HEAAL) 63 . However, post‐hoc analysis of the landmark ACE‐I trials in HF show that ACE‐I do not reduce the slope of GFR decline in comparison to patients assigned to placebo, but the short duration of follow‐up and early assessment of eGFR limit the interpretation of slope changes 64,65 . In contrast, in patients with diabetes (with or without HF), ACE‐I and ARBs do reduce the slope of GFR decline over time in trials of similar duration, which probably relates to the fact that diabetes is associated with more intraglomerular hypertension 68 .…”
Section: Renal Effects Of Established Guideline‐recommended Heart Fai...mentioning
confidence: 99%
“…63 However, post-hoc analysis of the landmark ACE-I trials in HF show that ACE-I do not reduce the slope of GFR decline in comparison to patients assigned to placebo, but the short duration of follow-up and early assessment of eGFR limit the interpretation of slope changes. 64,65…”
Section: Trial Evidence Of Renal Effects Of Ace-i and Arbmentioning
confidence: 99%
“…However, there was also no clear beneficial effect in these patients. 21,27,29 Data about ARBs in patients with CKD stage 4 are limited as well; however, although CIs were large, data might suggest a trend toward benefit in reducing cardiovascular death and HF hospitalization. 30 No information on ARB therapy is available in patients with CKD stage 5.…”
Section: Study Characteristics Of Landmark Clinical Trials: Baseline ...mentioning
confidence: 99%
“…[17][18][19] However, acute and sustained declines in eGFR have been observed in post-hoc analyses of trials of RAS inhibitors and MRAs in patients with HFrEF. [5][6][7][8] Moreover, post-hoc analyses of individuals with HFpEF from the CHARM programme 10 and I-PRESERVE studies 11 have reported an accelerated decline in renal function with the use of angiotensin receptor blockers, compared with placebo, suggesting that the pathophysiology of renal dysfunction in heart failure may be different from that observed in patients with CKD and type 2 diabetes mellitus. 20 In addition to providing RAS inhibition, combined angiotensin-neprilysin inhibitors simultaneously augment the endogenous natriuretic peptide system, with early studies of omapatrilat reporting fewer adverse renal impairment events, compared with enalapril, in patients with HFrEF.…”
Section: Discussionmentioning
confidence: 99%